Assessment of knowledge, attitudes, and practices of bushmeat value chain actors in Nigeria toward mpox and other zoonoses - Muhinda, Otto Vianney; Adedeji, Adeyinka Jeremy; Zirra, Abraham Albert; Dahourou, Laibané Dieudonné; Majekodunmi, Ayodele O.; Atuman, Yakubu Joel; Olubade, Toyin; Sabah, Mathew; Emikpe, Benjamin (Frontiers in Veterinary Science, 2025)
BackgroundThe bushmeat trade is a vital source of protein and income in Nigeria but presents significant public health risks due to its potential zoonotic disease transmission. Despite these risks, there has been limited exploration of the knowledge, attitudes, and practices (KAP) of individuals involved in the bushmeat value chain in Nigeria, particularly concerning food safety and transmission of wildlife related zoonoses such as mpox and others.MethodsA cross-sectional survey was conducted across three Nigerian states - Lagos, Rivers, and Bauchi - selected for their significant bushmeat trade activities and burden of zoonoses such as mpox and Lassa Fever. Using purposive sampling, data were collected from 238 participants (74 hunters, 115 traders, and 49 consumers) through structured questionnaires using Kobotools. Knowledge, attitudes, and practices of these value chain actors relating to disease transmission risk, handling and consumption of wildlife were evaluated.ResultsKnowledge of zoonotic disease transmission was limited, particularly among hunters (8.1%), traders (10.4%), and consumers (12.2%). Attitudes toward zoonotic disease risk were largely risky, with most actors underestimating the health risks associated with bushmeat handling. Results of practices of the value chain actors, revealed poor hand hygiene practices and poor usage of personal protective equipment (PPE) such as after wildlife handling, further amplified the public health risks. Educational level emerged as a significant predictor of knowledge and attitudes, but not practices, with tertiary-educated participants displaying significantly higher knowledge and positive attitudes (p < 0.05).ConclusionThis study reveals critical knowledge deficits and risky attitudes and practices within the bushmeat value chain. Results indicate urgent need for targeted, culturally sensitive, public health interventions to improve knowledge of mpox and other zoonoses identification and transmission, attitudes toward the risk of wildlife as reservoirs of mpox mpox and other zoonoses. And finally, improvement of hygienic practices and usage of appropriate PPE along the bushmeat value chain.